Laser Capture Microdissection: From Genomes to Chromosomes, from Complex Tissue to Single-Cell Analysis - Janíček, Tomáš; Hobza, Roman; Hudzieczek, Vojtěch (Methods in molecular biology (Clifton, N.J.), 2023)
Laser microdissection (LM) is a powerful tool for various molecular analyses providing pure samples for genomic, transcriptomic, and proteomic studies. Cell subgroups, individual cells, or even chromosomes can be separated via laser beam from complex tissues, visualized under the microscope, and used for subsequent molecular analyses. This technique provides information on nucleic acids and proteins, keeping their spatiotemporal information intact. In short, the slide with tissue is placed under the microscope, imaged by a camera onto a computer screen, where the operator selects cells/chromosomes based on morphology or staining and commands the laser beam to cut the specimen following the selected path. Samples are then collected in a tube and subjected to downstream molecular analysis, such as RT-PCR, next-generation sequencing, or immunoassay.
Keywords: Chromosomes; Proteomics; Laser Capture Microdissection; Microdissection; genom; Genome; Cells; Single-Cell Analysis; Histology; analýza jednotlivých buněk; laserová záchytná mikrodisekce; proteomika; Cytology; chromozomy